10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Enterohemorrhagic Escherichia coli (EHEC) remains one of the most prevalent foodborne pathogens and a continuing global public health concern. Infections have been reported worldwide and are most often linked to the consumption of raw or undercooked beef, unpasteurized dairy products, inadequately washed vegetables, and contaminated water-all reflecting the organism's persistence across the farm-to-fork continuum. This review summarizes recent advances in the epidemiology, molecular pathogenesis, and prevention of EHEC infection to provide an updated understanding of its transmission and control. It integrates data from surveillance systems, outbreak investigations, and molecular studies to bridge clinical, environmental, and food-safety perspectives. Temporal and geographical trends in EHEC prevalence are examined, highlighting variations in surveillance capacity, diagnostic accessibility, and hygiene standards that influence global prevalence estimates. The review further underscores the increasing contribution of non-O157 serotypes (O26, O103, O111, O145, O45, and O121) in several regions and the substantial economic burden associated with major outbreaks. The pathogen's complex virulence mechanisms are explored, focusing on the locus of enterocyte effacement and the Shiga toxins (Stx1 and Stx2), which mediate intestinal colonization and systemic complications such as hemolytic-uremic syndrome (HUS). Current treatment approaches are discussed, emphasizing the lack of safe antibiotic options, the importance of early supportive therapy, and emerging alternatives including monoclonal antibodies, probiotics, and vaccine-based interventions. Preventive strategies-such as Hazard Analysis and Critical Control Points (HACCP) systems, Good Agricultural Practices (GAP), and cattle vaccination-are outlined within a One Health framework. Understanding the molecular and epidemiological aspects of EHEC infection is essential for developing sustainable prevention and control policies through continued interdisciplinary research and international collaboration.